Impact of COVID-19 on dengue: a twofold challenge to public health in Sabah, Malaysia - Krishnan Nair Balakrishnan; Ping-Chin Lee (The Journal of Infection in Developing Countries, 2024)
Introduction: The dengue epidemic poses a significant public health challenge in Malaysia, and the concurrent presence of dengue and SARSCoV-2 infections has further strained its healthcare system. Sabah, the second largest state in Malaysia, located in the northern part of Borneo Island, has been particularly hard-hit by both dengue and SARS-CoV-2 outbreaks. This study aims to analyze the status of dengue infections in Sabah over the past decade and understand the impact of the COVID-19 pandemic on dengue virus transmission. Methodology: This study compared the annual dengue cases and associated deaths in Sabah from 2012 to 2022. Systematic data and information were collected from PubMed, the World Health Organization, the Centers for Disease Control and Prevention, and the official government reporting system of Malaysia. Results: Dengue cases in Sabah increased overall with slight fluctuations over the years, marked by new outbreaks approximately every 3-5 years. The number of deaths did not consistently correlate with reported dengue cases. Early in the COVID-19 pandemic in 2020, dengue cases remained high; however, as COVID-19 cases surged, dengue cases experienced a significant decline. Conversely, from mid-2022, dengue cases surged in Sabah despite COVID-19 cases remaining relatively low and well-controlled. Particularly noteworthy is the 99% increase in dengue cases in Sabah, contrasting sharply with Malaysia’s overall 36% decrease in 2022 compared to 2015 to 2019. Conclusions: Monitoring and prioritizing efforts to prevent COVID-19 and control dengue transmission is crucial. The dual challenges posed by these diseases offer valuable lessons that should be incorporated into future pandemic-preparedness strategies.